Deweys bevidsthedsbegreb - Kauffmann, Oliver (Studier i Pædagogisk Filosofi, 2012)
John Dewey has played a major role for philosophy of education and for educational theory as such. This paper deals with Dewey’s conception of consciousness, an issue which is rarely dealt with. It is claimed that Dewey’s thoughts on this issue are original and has actuality in the light of recent attempts to understand cognition and consciousness as intimately related to the subject’s interaction with the environment.